1999
DOI: 10.1046/j.1469-0705.1999.13050327.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging supplements ultrasonographic imaging of the posterior fossa, pharynx and neck in malformed fetuses

Abstract: MRI proved to be a valuable supplementary method to ultrasound in obtaining accurate information from the fetal neck, pharynx and posterior fossa, particularly when acoustic shadowing by bony structures or adjacent malformation impaired the quality of the ultrasonographic examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 16 publications
2
28
0
3
Order By: Relevance
“…From the literature it is clear that in case of bleeding, ischemic abnormalities, hemangiomas and hamartomas, the T1 sequence is preferred [19,24]. In this study there was 1 patient with intraventricular hemorrhage, 1 fetus with PVL and 1 fetus with cavernoic hemangioma and lymphangiomas.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…From the literature it is clear that in case of bleeding, ischemic abnormalities, hemangiomas and hamartomas, the T1 sequence is preferred [19,24]. In this study there was 1 patient with intraventricular hemorrhage, 1 fetus with PVL and 1 fetus with cavernoic hemangioma and lymphangiomas.…”
Section: Discussionmentioning
confidence: 70%
“…Sonography of a normal posterior fossa anatomy may be difficult because of shadowing from the fetal skull or engaging of the fetal head in the third trimester of pregnancy. MR is helpful in obtaining images on abnormalities in the posterior fossa [20,24,24]. In our 3 patients referred for cerebellar anomalies, a correct diagnosis could be made.…”
Section: Discussionmentioning
confidence: 83%
“…According to our results, discrepancies between US and MRI findings were often related to structures located in the posterior fossa. Poutamo et al [27] reported that the anatomy of the posterior fossa remained unclear in 8 of 19 cases on US and in one of 19 cases on MRI. Also Oh et al [28] highlighted that for these common posterior fossa anomalies understanding of the anatomy is essential to avoid pitfalls and misdiagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Fetal MR imaging is now acknowledged as the method of choice to delineate posterior fossa malformations in a fetus. [21][22][23] However, MR imaging findings in fetuses at risk for JSRD were only reported in the literature in 2 case reports. 24,25 The positive and negative predictive values of MR imaging findings for diagnosing JSRD in utero are not yet known.…”
mentioning
confidence: 99%